PENGARUH PENAMBAHAN VERMIKULIT TERHADAP KUAT LENTUR BETON MUTU RENDAH DENGAN SIMULASI BANJIR AIR LAUT - Syahril, Syahril; Mujiman, Mujiman; Prayogo, R Desutama Rachmat Bugi; Riandi, Muhammad Raihan; Uli, Pita; Artanti, Lintang D.; Shaputra, Muhammad Rio Eka (Politeknik Negeri Semarang, 2023)
The condition of high tides causing flooding or what is called tidal flooding is a condition that has a negative impact on the surrounding area, especially construction buildings. Construction buildings that are submerged in sea water can experience corrosion in the building structure. The addition or substitution of certain ingredients that can minimize the influence of minerals and salts contained in sea water, such as vermiculite, can be an alternative to this problem. Vermiculite material has the ability to absorb water and can extract heavy metal salts from water. This research was carried out by adding vermiculite to the concrete mixture at 0% (normal concrete), 12%, 24% and 36%, which was then tested on fresh concrete mixture (slump and bulk density testing). The test object used is in the form of a block with dimensions of 100mm Ã— 100mm Ã— 500mm. Concrete flexural strength testing was carried out on test objects that had been soaked using sea water and ordinary water as a comparison. The highest flexural strength value of concrete was in the mixture with a percentage value of 36%, namely 2.91 MPa for concrete submerged in sea water and 2.86 MPa for concrete submerged in plain water. The addition of vermiculite material can increase the flexural strength value of concrete along with the percentage level of the vermiculite mixture.